Measurement of iron chemical speciation in seawater at 4 °C: the use of competitive ligand exchange–adsorptive cathodic stripping voltammetry - Hassler, CS; Legiret, F-E; Butler, ECV (2013)
Iron is mostly bound to poorly characterised organic ligands; thus, organic ligands are paramount in defining Fe biogeochemical cycling and its control on oceanic primary productivity. Since 1994, Fe chemical speciation has been determined by Competitive Ligand Exchange–Adsorptive Cathodic Stripping Voltammetry (CLE–AdCSV) at room temperature. However, chemical speciation is strongly dependent on temperature and some organic ligands can be temperature sensitive. Here, we compare the use of the CLE–AdCSV at room temperature and at 4 °C—a temperature closer to that found in the Southern Ocean, one of the largest iron-limited regions. For both temperatures, similar detection limits and total Fe concentrations were found. However, at 4 °C the analytical detection window (α Fe(TAC) 2 ) was shifted by 1.4-fold towards the detection of weaker ligands, resulting in up to 2-fold lower ligand concentrations as well as a 2- to 5-fold and 10- to70-fold lower conditional stability constants with inorganic Fe (Fe′) and Fe(III), respectively. As a result, the Fe′ concentration at 4 °C was 2-fold greater, resulting in direct implication for Fe bioavailability. Results show that difference in Fe chemical speciation at 4 °C was not solely explained by temperature effect on thermodynamics with the exchange ligands or the diffusion of the electroactive complex towards the Hg drop. Lowering analytical window during analysis at room temperature is proposed as a first estimate of temperature effect on iron chemical speciation.